2001
DOI: 10.1086/323993
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Virus–Encoded Proteins Reflect Murine Cytomegalovirus Productivity in Organs

Abstract: Mouse infection with murine cytomegalovirus (MCMV) is an established model for studying human cytomegalovirus infection. In this study, the relationship was analyzed between MCMV activity in organs of infected mice and the presence of infectious virus (viremia), viral genomes (DNAemia), or secreted virus-encoded proteins in the blood. For the latter, 2 recombinant viruses were constructed that encode for the hepatitis B virus surface antigen and the secreted alkaline phosphatase, respectively, as secreted mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Our data show for the first time that a herpesvirus infection can be launched directly from bacteria carrying the infectious virus genome, omitting the need for technical preparatory work to isolate BAC DNA. We have also demonstrated that additional genes introduced into the virus are effectively expressed (3). Thus, the use of BAC-derived viruses has a potential as vaccine and vaccine vector, and this is also the case when the viral genome is launched from bacteria.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our data show for the first time that a herpesvirus infection can be launched directly from bacteria carrying the infectious virus genome, omitting the need for technical preparatory work to isolate BAC DNA. We have also demonstrated that additional genes introduced into the virus are effectively expressed (3). Thus, the use of BAC-derived viruses has a potential as vaccine and vaccine vector, and this is also the case when the viral genome is launched from bacteria.…”
Section: Discussionmentioning
confidence: 85%
“…Plasmid pRep4-HBs was generated by inserting the gene of the hepatitis B virus surface antigen (HBsAg) into pRep4 (Invitrogen) as described (3). To obtain MCMV-HBs, the HBs gene bracketed by a Rous sarcoma virus promoter and a simian virus 40 polyadenylation signal was excised from pRep4-HBs and inserted into the ie2 gene locus of the cloned full-length MCMV BAC, pSM3fr (37), as previously described (3).…”
Section: Methodsmentioning
confidence: 99%
“…(A) Virus yield (log) per gram of homogenized liver and brain determined by plaque assay and results expressed as infectious units (PFU)/g of tissue as described previously (reference 21). (B) Real-time PCR performed with MCMV IE-1 primers using DNA extracted from the livers or brains of infected animals as described in Results and Materials and methods, expressed as IE-1 copy number per 200 μl of 10% homogenate as a function of time after infection (reference 77). (C–F) IHC detection of virus-infected cells using anti-pp89 (IE-1) in (C) the frontal cortex from a PN day 12 mouse, (D) in neurons of hippocampus from a PN day 11–infected mouse, (E) granular neurons of cerebellum, and (F) Purkinje neurons of cerebellum from PN day 11 mice.…”
Section: Resultsmentioning
confidence: 99%
“…For dexa experiments, organs were collected, weighed and homogenized. A 10% homogenate in media was utilized for standard plaque assays [134]. For pred experiments, organs were collected and DNA was isolated using Trizol according to the manufacturer's instructions (Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%